Cisplatin, Chemotherapy Agent: Production of Reference Standard for Products Determination - Ambarsari, Christy (Rifa'Institute, 2026)
Introduction: Cisplatin is a cytotoxic drug that is used as cancer therapy. To ensure the success of treatment, the drug products must be examined using reference standards. Objective: Cisplatin has been developed as a reference standard for the quantification of products, both pre-market and post-market. Method: The conducted tests included FTIR assays, water content analysis, impurity assay, and homogeneity evaluation. Result and Discussion: The RP-HPLC assay results demonstrated the qualified suitability, linearity, and accuracy. The homogeneity test yielded a linearity represented by the equation y = 5.668.152,75x + 411,5 (r =1). The response factor deviation indicated an accuracy of 0,23%, and homogeneity was confirmed with Fcal = 0,17 (Ftable = 3,02). Conclusions: Cisplatin can be used as a reference standard, with an assigned value of 97,15% (U = 1,43%).